2016
DOI: 10.1159/000444683
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Dysfunction Increases Mortality and Incident Events after Young Stroke: The FUTURE Study

Abstract: Background: In about 30% of young stroke patients, no cause can be identified. In elderly patients, kidney dysfunction has been suggested as a contributing risk factor for mortality as well as stroke. There are hypotheses that novel non-traditional risk factors, like chronic inflammation and oxidative stress, are involved in chronic kidney disease, affecting the cerebral microvasculature that would in turn lead to stroke. Our objective is to investigate the influence of kidney dysfunction on long-term mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 32 publications
(43 reference statements)
1
17
1
Order By: Relevance
“…Consequently, these two conditions might partly mediate the association between insomnia and death. Some studies found that patients with stroke who also had CVD or kidney dysfunction had a higher risk of death 15 36. In this study, subjects with severe physical illness were excluded, which might explain the weak statistical power of the result.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Consequently, these two conditions might partly mediate the association between insomnia and death. Some studies found that patients with stroke who also had CVD or kidney dysfunction had a higher risk of death 15 36. In this study, subjects with severe physical illness were excluded, which might explain the weak statistical power of the result.…”
Section: Discussionmentioning
confidence: 85%
“…Medical history, past psychiatric diagnosis, vascular risk factors (eg, history of hypertension, diabetes and smoking), clinical characteristics such as type of stroke and National Institute of Health Stroke Scale (NIHSS) score for the first time after admission, and other medical complications (eg, atrial fibrillation, urinary disease and tumours) were also collected at intake time. Exclusion criteria were patients who had a history of stroke; patients with obvious aphasia that impeded the patient from finishing psychological assessment; patients who withdrew from follow-up at any of the following time points; and patients with severe heart disease or nephropathy or tumour, or a history of psychiatric diagnosis, as the above conditions were shown to be associated with insomnia and mortality 15 16…”
Section: Methodsmentioning
confidence: 99%
“…Evidence not only suggests that RD is an independent risk factor for cardiovascular events, including stroke and myocardial infarction [13,14,15], but also indicates that RD is associated with worse functional and clinical outcome in ischemic stroke patients [4,16]. …”
Section: Introductionmentioning
confidence: 99%
“…In addition, distinctive risk profiles, mechanisms of stroke, and racial disparities have been suggested in several population studies of ischemic stroke in the dialysis population 2, 3, 4, 5, 6, 7, 8, 9. Dialysis status has also been shown to be an independent predictor of in‐hospital mortality following acute stroke 2, 5, 10, 11, 12. However, contemporary studies focusing on the incidence, characteristics, and outcomes of acute ischemic stroke (AIS) in patients on maintenance dialysis are sparse.…”
mentioning
confidence: 99%